2016
DOI: 10.1038/nchembio.2059
|View full text |Cite
|
Sign up to set email alerts
|

Raft-based interactions of gangliosides with a GPI-anchored receptor

Abstract: Gangliosides, glycosphingolipids containing one or more sialic acid(s) in the glyco-chain, are involved in various important physiological and pathological processes in the plasma membrane. However, their exact functions are poorly understood, primarily because of the scarcity of suitable fluorescent ganglioside analogs. Here, we developed methods for systematically synthesizing analogs that behave like their native counterparts in regard to partitioning into raft-related membrane domains or preparations. Sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
204
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(218 citation statements)
references
References 61 publications
13
204
1
Order By: Relevance
“…In comparison, identically labeled phosphatidylethanolamine appeared to diffuse freely in the membrane (Eggeling et al, 2009), which implied that lipid-cytoskeleton interactions were not responsible for the anomalous cholesterol-dependent sphingolipid diffusion. Noteworthy, this finding of unhindered phosphatidylethanolamine diffusion conflicts with a previous single molecule tracking study (Fujiwara et al, 2002), and subsequent STED-FCS and single molecule tracking studies reported by these authors and others (Andrade et al, 2015; Fujiwara et al, 2016; Komura et al, 2016). Although, the authors of the STED study never concluded that the cholesterol-dependent trapping of sphingomyelin, GM1 and GPI-anchored proteins was indicative of tiny lipid rafts, their results were often cited by others as support for the lipid raft hypothesis (Lingwood and Simons, 2010; Levental and Veatch, 2016).…”
Section: Super-resolution Fluorescence Imaging Of Fluorescent Sphingocontrasting
confidence: 90%
See 1 more Smart Citation
“…In comparison, identically labeled phosphatidylethanolamine appeared to diffuse freely in the membrane (Eggeling et al, 2009), which implied that lipid-cytoskeleton interactions were not responsible for the anomalous cholesterol-dependent sphingolipid diffusion. Noteworthy, this finding of unhindered phosphatidylethanolamine diffusion conflicts with a previous single molecule tracking study (Fujiwara et al, 2002), and subsequent STED-FCS and single molecule tracking studies reported by these authors and others (Andrade et al, 2015; Fujiwara et al, 2016; Komura et al, 2016). Although, the authors of the STED study never concluded that the cholesterol-dependent trapping of sphingomyelin, GM1 and GPI-anchored proteins was indicative of tiny lipid rafts, their results were often cited by others as support for the lipid raft hypothesis (Lingwood and Simons, 2010; Levental and Veatch, 2016).…”
Section: Super-resolution Fluorescence Imaging Of Fluorescent Sphingocontrasting
confidence: 90%
“…Instead, alternative hypotheses that do not involve cohesive sphingolipid-cholesterol interactions must be developed, investigated, and discarded if they prove inconsistent with experimental results. These alternative hypotheses should account for the following observations: The diffusion and distribution of proteins and lipids is influenced by the actin cytoskeleton (Fujiwara et al, 2002, 2016; Mueller et al, 2011; D'Auria et al, 2013; Frisz et al, 2013a,b; Honigmann et al, 2014; Andrade et al, 2015; Sevcsik et al, 2015; Komura et al, 2016). …”
Section: Implications For Plasma Membrane Organization Hypothesesmentioning
confidence: 99%
“…[8] Meanwhile, arabinosyld onor 14 was reactedw ith galactosyl acceptor 13 upon the activation by Crich's promoter system, [17] yielding Arafa (1,4)Gal sequence 18 in excellent yield without destroying the allyl ether moiety.A gain, the disaccharide underwent conversion into glycosyli midate donor 20 by following as imilar procedure to that for 17.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, most SR experiments are conducted in chemically fixed cells or membrane sheets 133, 152, 153 , and these preparations can be prone to artifacts because lipids and even some membrane proteins are not immobilized by most fixation protocols 154 . Experiments in live cells are possible, but require experimental and analytical methods that anticipate the fast dynamics expected for raft structures 155, 156 .…”
Section: Detecting Rafts Using Super-resolution Microscopymentioning
confidence: 99%
“…Several approaches that do not rely in image reconstruction have had some success in this area. A recent advance definitively correlated three distinct measures of raft association – DRMs association, ordered phase portioning in GPMVs, and surface patching in live cells – across more than a dozen probes, along with probing the lifetime of the small entities in unperturbed cells, using multi-color single particle tracking 156 . This study has provided some of the strongest evidence to date to link classical raft observations with novel model membranes and modern imaging techniques.…”
Section: Detecting Rafts Using Super-resolution Microscopymentioning
confidence: 99%